In vitro inhibitory effects of plant-derived by-products against Cryptosporidium parvum - Teichmann, Klaus (EDP Sciences, 2016)

(untitled) (Parasite)
Disposal of organic plant wastes and by-products from the food or pharmaceutical industries usually involves high costs. In the present study, 42 samples derived from such by-products were screened in vitro against Cryptosporidium parvum, a protozoan parasite that may contaminate drinking water and cause diarrhoea. The novel bioassay was previously established in the microtitre plate format. Human ileocaecal adenocarcinoma (HCT-8) cell cultures were seeded with C. parvum oocysts and parasite development was monitored by an indirect fluorescent antibody technique (IFAT) and microscopic assessment for clusters of secondary infection (CSI). Minimum inhibitory concentrations (MICs) and potential detrimental effects on the host cells were determined. An ethanolic extract from olive (Olea europaea) pomace, after oil pressing and phenol recovery, reproducibly inhibited C. parvum development (MIC = 250–500 μg mL(−1), IC(50) = 361 (279–438) μg mL(−1), IC(90) = 467 (398–615) μg mL(−1)). Accordingly, tyrosol, hydroxytyrosol, trans-coniferyl alcohol and oleuropein were selected as reference test compounds, but their contributions to the observed activity of the olive pomace extract were insignificant. The established test system proved to be a fast and efficient assay for identifying anti-cryptosporidial activities in biological waste material and comparison with selected reference compounds.